2021
DOI: 10.1186/s12889-021-11203-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in equity of inpatient health service utilization for the middle-aged and elderly in China: based on longitudinal data from 2011 to 2018

Abstract: Background The aim of this study was to assess the trends in equity of receiving inpatient health service utilization (IHSU) in China over the period 2011–2018. Methods Longitudinal data obtained from China Health and Retirement Longitudinal Studies were used to determine trends in receiving IHSU. Concentration curves, concentration indices, and horizontal inequity indices were applied to evaluate the trends in equity of IHSU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…Chronic diseases have contributed to the inequitable outcome for the rich. Consistent with other studies ( 16 , 52 ), chronic diseases are also associated with medical expenditures. Persons with disabilities likely have overlapping functional limitations or complex health conditions that present higher medical needs, thus leading to higher medical expenditure ( 53 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Chronic diseases have contributed to the inequitable outcome for the rich. Consistent with other studies ( 16 , 52 ), chronic diseases are also associated with medical expenditures. Persons with disabilities likely have overlapping functional limitations or complex health conditions that present higher medical needs, thus leading to higher medical expenditure ( 53 ).…”
Section: Discussionsupporting
confidence: 91%
“…The concentration and horizontal inequity indices were positive, indicating a pro-rich inequality in medical expenditure, whereby people with high-economic status had more medical expenses than those with low-economic status. The income-related inequality results of people with disabilities differed from the inpatient service utilization of middle-aged and older adults ( 16 ), and the inequality was lower than in people with hypertension ( 38 ). This implied that access to health services for persons with disabilities requires a higher economic level, and some health policies for vulnerable groups may help alleviate disability inequities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Considering the substantial socioeconomic gap between rural and urban areas in China, rural residents are more likely to encounter obstacles (long distance from medical institutions, inconvenient transportation, and insufficient supply of specific experts), 11 therefore, we analyzed rural and urban samples.…”
Section: Methodsmentioning
confidence: 99%
“…Abundant studies supported the notion that income-related inequality in rural areas existed a strong pro-poor inequality of CHE by the methods of concentration index, treatment-effect model, or chi-square tests [9][10][11][12][13][14]. Besides, a growing number of studies reported that economic status, education levels, lifestyle, households with elderly, with disabilities or chronic diseases, and other factors were the critical risk factors for CHE and its inequality [15][16][17]. Therefore, identifying income-related inequality of CHE is merit in developing appropriate strategies and further achieving health equality for rural China.…”
Section: Introductionmentioning
confidence: 99%